An Analysis of the Causes of Divorce among Muslims in Mombasa County in the Sharia Law Perspective - Abdulrahman, Manswab Mahsen (IJISH (International Journal of Islamic Studies and Humanities), 2020)
Divorce is the most hateful action permitted in Islamic law. Islam puts some measures to ensure that the separation of two spouses will not occur. However, on some occasions, dissolution will become necessary because two parties cannot live together in an atmosphere of hatred and disaffection. Recently, cases about the repeal have been increasing rapidly among Muslim society in Mombasa County. This study explores the issues causing divorce among spouses in Mombasa County. The result shows that some of the reasons for divorce are poverty and unemployment, seeking a job overseas, psychological problems, drug addiction, family interference, early and forced marriage, cultural issues, and domestic violence. Questionnaire and Open-ended questions were used involving divorcees as respondents. In addition to that, the researcher reviewed references and studied dissertations relating to divorce.